THE PROBLEMATICS OF IMPLEMENTING THE “KURIKULUM MERDEKA” IN ENGLISH SUBJECTS AT SD INPRES 125 BAJENG - Putri Nurhandayani; Jusmaniar N; Sulviana Sulviana (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
The purpose of this research is to identify teachers' problems in the implementation of the “Kurikulum Merdeka” in English language subjects at SD Inpres 125 Bajeng in the 2023/2024 school year. In this research, researcher used a qualitative descriptive design. Researcher collected data through interviews with principals, homeroom teachers, and students in grades I, II, IV, and VI. The results of this research reveal that teachers lack understanding of learning models related to the “Kurikulum Merdeka”, and teachers still need time to adapt to the “Kurikulum Merdeka”. In addition, the teacher's English language skills are still lacking so the teacher states that there is a need for an English teacher with an English education background, the teacher also needs training related to the “Kurikulum Merdeka”, and inadequate English learning facilities. Furthermore, some factors inhibit the implementation of the “Kurikulum Merdeka”, such as internal factors and external factors. Internal factors consist of some students who show disinterest when learning English subjects, students who have difficulty in understanding learning materials and find the learning process uninteresting, mostly due to dissatisfaction with learning methods. Therefore, the external factors that inhibit the implementation of the "Kurikulum Merdeka” ‘consist of grade IV students who express their dissatisfaction with the English teaching methods used in their class and teachers’ lack of understanding in using technological media which results in a less-than-optimal learning process.